2021
DOI: 10.1002/pei3.10065
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variation in the response of soybean to elevated CO2

Abstract: In the 20 million years preceding the industrial revolution, atmospheric CO 2 concentration in the atmosphere was below 280 ppm but continued to increase since then and reached almost 410 ppm (http://www.esrl.noaa.gov/gmd/ccgg/trend s/) by 2020. In the future, with current trends, it will probably exceed 550 ppm by 2050 (IPCC, 2014). Therefore, plants are facing unprecedented levels of CO 2 concentration, and it is highly questionable that they could adapt to this change so quickly (Bishop et al., 2015). Sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
0
9
2
Order By: Relevance
“…Several studies have shown that seed mineral content and its response to eCO 2 was highly dependent on the environment (Dier et al, 2020;Fernando, Panozzo, Tausz, Norton, Fitzgerald, Myers, et al, 2012;Fernando, Panozzo, Tausz, Norton, Neumann, et al, 2014;Köhler et al, 2019;Parvin et al, 2019;Samarah et al, 2004;Singh et al, 2016) as well as the cultivar (Beleggia et al, 2018;Myers et al, 2014). Soares et al (2021) also reported stronger declines when using a FACE setting compared with experiments performed in growth chambers (Soares et al, 2019), emphasizing that the experimental set can also affect the results (Bunce, 2016). More studies are needed to improve our mechanistic understanding of the interaction of eCO 2 and growing season conditions and their effects on seed nutrient content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that seed mineral content and its response to eCO 2 was highly dependent on the environment (Dier et al, 2020;Fernando, Panozzo, Tausz, Norton, Fitzgerald, Myers, et al, 2012;Fernando, Panozzo, Tausz, Norton, Neumann, et al, 2014;Köhler et al, 2019;Parvin et al, 2019;Samarah et al, 2004;Singh et al, 2016) as well as the cultivar (Beleggia et al, 2018;Myers et al, 2014). Soares et al (2021) also reported stronger declines when using a FACE setting compared with experiments performed in growth chambers (Soares et al, 2019), emphasizing that the experimental set can also affect the results (Bunce, 2016). More studies are needed to improve our mechanistic understanding of the interaction of eCO 2 and growing season conditions and their effects on seed nutrient content.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the impact of eCO 2 on Ca, Zn, and Fe has received considerable attention because of their importance to human health (FAO et al., 2021). Several studies have reported a decline in one or more of these elements in soybean (Li et al., 2018; Soares et al., 2021; Soba et al., 2020), other legumes (Högy et al., 2009; Parvin et al., 2019; Saha et al., 2015), and other C 3 crops (Chumley & Hewlings, 2020; Högy et al., 2009; Zhu et al., 2018). Those three elements were also shown to decline under eCO2 in our study, although not consistently in both cultivars and all years.…”
Section: Discussionmentioning
confidence: 99%
“…All models assume that the seed protein concentration will remain largely unaffected by elevated temperature and CO 2 levels, meaning that soybean yields translate directly into protein yields. Experimental evidence, however, indicates that soybean seed protein may decrease slightly under elevated CO 2 levels (Li et al, 2018; Soares et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental evidence, however, indicates that soybean seed protein may decrease slightly under elevated CO 2 levels (Li et al, 2018;Soares et al, 2021).…”
Section: Agroecosystem Modelsmentioning
confidence: 99%
“…Well-founded research must support this transition, evidencing how future climate events will impact food safety and nutritional profile, given that current data mainly focuses on crop production in face of weather variables ( Marmai et al., 2022 ). However, there are few recent studies that suggest that the increasing CO 2 levels, heat, drought, or salinity stresses, either single or combined, alter nutrient allocation pathways and accumulation in staple crops, such as soybean and wheat ( Soares et al., 2021 ; Zhara et al., 2022 ).…”
mentioning
confidence: 99%